Who should price a gig? : successful platforms must balance economic considerations and power dynamics with providers and customers as they determine who sets prices - Karanovic, Jovana; Altman, Elizabeth J.; Cennamo, Carmelo (MIT Sloan Management Review, 2023)
One of the most consequential governance questions for platform operators is deciding who sets prices and what discretion other parties in the transaction have to alter them. Putting the locus of control primarily in the hands of the platform provider presents drawbacks but so does allowing other stakeholders to set prices, if prices set too high or too low limit participation on the platform. The authors advocate for a hybrid approach that shares some control.